Kinematic analysis of the volleyball back row jump spike - Huang, C.; Liu, G. -C.; Sheu, T. -Y. (1999)
The purpose of this study was to identify and describe the kinematic characteristics of the volleyball one-foot and two-foot back row jump spikes. Eight elite male players participated in this study. Two Peak high-speed cameras (120Hz) were synchronised to record the spiking action. The results indicated that the one-foot spike had a greater approach, centre of mass (CM) velocity, a greater horizontal CM velocity at takeoff and a shorter spiking time than that of the two-foot spike. The swing leg of the one-foot jump spike also played an important role in contributing forward momentum to the jump during the support phase.This study provides information for coaches in teaching the volleyball one-foot and two-foot back row jump spike.